Visiones críticas en torno a los deportes a fines del siglo XIX. (2014)
This paper presents and analyzes the criticisms made by intellectuals of the nineteenth century towards sports. From different fields of knowledge (evolutionary philosophy, anthropology and economics) Herbert Spencer (1860/1904), Edward Tylor (1881/1973) and Thorstein Veblen (1899/2005) agreed to question the primacy of sports over traditional practices, rituals and folk. These authors, without reaching the ends of the luddites respect of industrial machines, extolled the unfavorable aspects of physical exercises, planting a seed of doubt that continues to this day. The importance of knowing these arguments lies in the way they faced the sporting phenomenon when it began to be institutionalized in a new set of corporal, transformative exercises and apparently a generator of fitness and health.